Bypass distal to the standing neck - Gastambide, Carmelo; Esperón, Alejandro; Pereira, Jorge; Martín, Juan J.; López, Daniel; Diamant, Marcelo (Cirugía del Uruguay, 1997)
The authors carry out a retrospective study of the results of 48 by-passes distal to the neck of the foot performed in 43 patients, 32 males and 11 females, with an average age of 70 years, during a 20 month period. The presence of hypertension (95%), coronary artery disease (95%) and diabetes 93%) in the series is pointed out.